Analisis Pengaruh Arus Kas Operasi, Laba Bersih, dan Hutang Terhadap Kebijakan Dividen Dimoderasi Good Corporate Governance - Hendra Saputra Frinando Marpaung; Herlin Tundjung Setijaning; Hendrian (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Profitable companies that face cash flow problems can cause losses even though they appear profitable in the financial statements. This study aims to analyze the effect of operating cash flow, net income, debt on dividend policy, and the role of corporate governance as a moderating variable. The results of the study are expected to provide insight for management and investors in formulating effective dividend policies and supporting better investment decision making. Data Analysis Methods include Descriptive Statistical Tests, Model Tests, Classical Assumption Tests, and various tests such as normality, multicollinearity, heteroscedasticity, autocorrelation, and determination coefficient tests (Adjusted R2), and simultaneous tests (F Test). The results of this study are that operating cash flow, net income, debt have a significant effect on dividend policy. Operating cash flow, net income, debt are moderated by Good Corporate Governance on dividend policy. Operating cash flow, net income, debt have a significant effect on dividend policy. Operating cash flow, net income, debt are moderated by Good Corporate Governance on dividend policy.